A cross sectional study on quality of sleep among adult population in an urban area of Pahang - Pasi, Hafizah; Mohd Rus, Razman; Abd. Aziz, Karimah Hanim; Yusof, Muhammad Zubir; Hassan, Noor Artika (2018)
Introduction: Sleep is one of the important needs in human life and good quality of sleep among adult population reduced the risk factor for adverse health outcome. This study aim to determine the quality of sleep and its related factors among adult population in an urban area of Pahang. Materials and method:Cross sectional study on a selected urban housing area in Pahang. Participants are adult population aged more than 18 years old (observation unit) in a selected houses (n=180). Measurements: respondent’s socio-demographic, co-morbidity, smoking status, physical activity, monthly household income and caffeinated drinks consumed were obtained via the questionnaire. The sleep quality was measured using the validated Pittsburgh Sleep Quality Index (PSQI).Results: A total of 145 respondents (response rate 81%) were available for data analysis. The prevalence of good sleeper (60%) was more than poor sleeper. Adjusted logistic regression done shows that only those who do not take caffeinated drinks the past one week have higher chance of having good quality of sleep as compare to those who take (OR=3.6, p=0.048). No other significant relationship seen between quality of sleep with socio-demographic characteristics, exercise or co-morbid history. Conclusion:Majority of adult population in this selected urban area in Pahang have good quality of sleep and result shows significant relationship between quality of sleep with not taking caffeinated drinks, but not other factors. Nevertheless, programs such as sleep quality awareness campaign need to be done to educate the population and maintain this good sleep quality.